A new publication on the history of Tuva (about the book by Z. Y. Dorzhu and O. Y. Irgit Рolitical repressions in the Tuva People’s Republic (1921–1944) – Novosibirsk, 2023) - S. A. Papkov (Омский научный вестник: Серия "Общество. История. Современность")
This analytical review focuses on the work of Tuvinian researchers on the causes and consequences of political purges in Tuva during the existence of the Republic as a formally sovereign state. The authors of the book consistently reconstruct the main cycle of socio-political events in the region, figuring out how the experience and practices of revolutionary Russia passed on to Tuvinian soil. The ways and peculiarities of promotion of new leading cadres in the Republic and development of inter-clan struggle for power, formation of unusual party-state system, which allowed its leaders to widely use punitive measures against their opponents are considered. The reviewed work vividly presents historical portraits of major leaders of Tuva, demonstrates methods and ways of their promotion to political avantgarde, as well as the tragic end of careers of many of them. The published book is evaluated as a major contribution to the historiography of Tuva, thanks to new facts and interpretations of socio-political events in Central Asia in the first half of the 20th century.